The Subsistence Perspective : Beyond the Globalised Economy - Maria Mies; Veronika Bennholdt-Thomsen (Zed Books, London/ Spinifex, Australia, 1999)
Originally published in German 1997. The author explains subsistence as empowerment based on peoples' own strengths and their co-operation with each other and with nature, rather than endless accumulation of wealth.
English
Keywords: HB1-3840 Economic Theory. Demography